Multifunctional Organic–Inorganic Hybrid Perovskite Microcrystalline Engineering and Electromagnetic Response Switching Multi‐Band Devices - Yan, Jun; Zheng, Qi; Wang, Shuang‐Peng; Tian, Yong‐Zhi; Gong, Wei‐Qiang; Gao, Feng; Qiu, Ji‐Jun; Li, Lin; Yang, Shu‐Hui; Cao, Mao‐Sheng (Advanced materials (Weinheim), 2023)
High‐efficiency electromagnetic (EM) functional materials are the core building block of high‐performance EM absorbers and devices, and they are indispensable in various fields ranging from industrial manufacture to daily life, or even from national defense security to space exploration. Searching for high‐efficiency EM functional materials and realizing high‐performance EM devices remain great challenges. Herein, a simple solution‐process is developed to rapidly grow gram‐scale organic–inorganic (MAPbX3, X = Cl, Br, I) perovskite microcrystals. They exhibit excellent EM response in multi bands covering microwaves, visible light, and X‐rays. Among them, outstanding microwave absorption performance with multiple absorption bands can be achieved, and their intrinsic EM properties can be tuned by adjusting polar group. An ultra‐wideband bandpass filter with high suppression level of −71.8 dB in the stopband in the GHz band, self‐powered photodetectors with tunable broadband or narrowband photoresponse in the visible‐light band, and a self‐powered X‐ray detector with high sensitivity of 3560 µC Gyair−1 cm−2 in the X‐ray band are designed and realized by precisely regulating the physical features of perovskite and designing a novel planar device structure. These findings open a door toward developing high‐efficiency EM functional materials for realizing high‐performance EM absorbers and devices. A facile one‐step solution processing method is developed to rapidly prepare gram‐scale MAPbX3 microcrystals. Utilizing its intrinsic electromagnetic (EM) properties, a series of EM devices is designed and fabricated, which can be applied in the fields of ultra‐wideband bandpass filters and multi‐band photodetection covering X‐rays, UV, visible light, and microwaves.